2014
DOI: 10.1186/s12858-014-0029-y
|View full text |Cite
|
Sign up to set email alerts
|

Folding and self-association of atTic20 in lipid membranes: implications for understanding protein transport across the inner envelope membrane of chloroplasts

Abstract: BackgroundThe Arabidopsis thaliana protein atTic20 is a key component of the protein import machinery at the inner envelope membrane of chloroplasts. As a component of the TIC complex, it is believed to form a preprotein-conducting channel across the inner membrane.ResultsWe report a method for producing large amounts of recombinant atTic20 using a codon-optimized strain of E. coli coupled with an autoinduction method of protein expression. This method resulted in the recombinant protein being directed to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The θ 208 /θ 222 ratios of the CD spectra, in both OG detergent and liposomes, were less than 1 (0.60, 0.63 and 0.61 for UCP2, UCP4 and UCP5 respectively). Such ellipticity ratios have been observed in the spectra of coiled coil and helical bundle motifs and as a result of protein association [22,3134]. Using complementary electrophoresis and MS methods, the atypical helical conformation of the neuronal UCPs can mostly probably be attributed to a predominant population of UCP multimers (tetramers) in liposomes with molecular mass of ∼ 140–150 kDa (Figures 2G–2I; Supplementary Table S1).…”
Section: Resultsmentioning
confidence: 75%
“…The θ 208 /θ 222 ratios of the CD spectra, in both OG detergent and liposomes, were less than 1 (0.60, 0.63 and 0.61 for UCP2, UCP4 and UCP5 respectively). Such ellipticity ratios have been observed in the spectra of coiled coil and helical bundle motifs and as a result of protein association [22,3134]. Using complementary electrophoresis and MS methods, the atypical helical conformation of the neuronal UCPs can mostly probably be attributed to a predominant population of UCP multimers (tetramers) in liposomes with molecular mass of ∼ 140–150 kDa (Figures 2G–2I; Supplementary Table S1).…”
Section: Resultsmentioning
confidence: 75%
“…The Tic20 gene family encodes an inner chloroplast membrane protein that likely functions as a channel for protein import (Kasmati et al, 2011;Kikuchi et al, 2013;Campbell et al, 2014). The severe tic20-iv phenotype on spectinomycin indicates that ACC2 is unable to enter the chloroplast and contribute to fatty acid biosynthesis when Tic20-IV is eliminated.…”
Section: Loss Of Tic20-iv-mediated Chloroplast Protein Import Resultsmentioning
confidence: 99%
“…Earlier studies performed on pea chloroplasts revealed several of its subunits, including Tic110, Tic62, Tic55, Tic40, Tic32, Tic22, and Tic20 (21,(24)(25)(26)(27)(28). However, there is no consensus as to which components form the proteinconducting channel: while multiple studies demonstrated a channel activity for Tic20 in vitro (42)(43)(44)(45), it is still debated whether Tic110 is also directly involved in forming a channel (46)(47)(48)(49). The scenario has been further complicated by the recent isolation of a novel large TIC complex in Arabidopsis, termed the "1-MDa complex" (42,44), that contains Tic20 in association with a different set of proteins, namely Tic100, Tic56 and Tic214.…”
Section: Introductionmentioning
confidence: 99%